A Review of Diabetes Mellitus Among Coastal Communities: Risk Factors and Public Health Implications - Safrina; Histina (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Diabetes mellitus is one of the most prevalent non-communicable diseases globally, with an increasing incidence observed in various regions, including coastal communities. Its prevalence in these areas is influenced by several factors, such as dietary patterns, levels of physical activity, educational attainment, and environmental and socio-economic conditions. Objective: This study aims to review existing literature related to diabetes mellitus in coastal areas to identify associated risk factors, health impacts, and effective prevention strategies. Method: A literature review approach was employed by analyzing relevant peer-reviewed journal articles that discuss the risk factors, prevalence rates, and intervention programs targeting diabetes in coastal populations. Results: The findings indicate that diets high in fat and sugar, sedentary lifestyles, and limited public awareness regarding health contribute significantly to the rising prevalence of diabetes in coastal areas. However, health education initiatives and community-based intervention programs have demonstrated effectiveness in lowering diabetes incidence. Conclusion: To reduce the burden of diabetes in coastal communities, it is essential to implement comprehensive prevention strategies, improve access to healthcare services, and strengthen health education programs. Keywords: diabetes mellitus, coastal communities, risk factors, health education, prevention strategies